UPAYA GURU DALAM MENANAMKAN NILAI MORAL MELALUI BUDAYA SEKOLAH PADA SISWA KELAS IV SD BUDI MULIA DUA SEDAYU YOGYAKARTA - Ismi Rahmiyati; Arip Febrianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation, forms of teacher efforts, supporting and inhibiting factors in instilling moral values ​​through culture in fourth-grade students of Budi Mulia Dua Elementary School. This study used a qualitative case study approach. The research subjects were the principal, teachers, and fourth-grade students of Budi Mulia Dua Elementary School. Data collection techniques included interviews, observation, and documentation. Data analysis employed the Miles and Huberman interactive analysis model, which included data reduction, data presentation, and conclusion drawing. Data validity was tested through triangulation of sources, techniques, and member checking. The results showed that the implementation of culture was carried out through positive habits, the creation of a conducive school environment, and the involvement of all school members in implementing character values. Teachers made various efforts through habituation, role modelling, providing advice, reinforcing positive behaviour, and implementing school rules. Supporting factors include the support of school policies, consistent school culture programs, teacher role models, a positive school environment, and collaboration between the school and parents. Inhibiting factors include differences in student character and awareness, the influence of the outside environment, and the development of social media, which can influence student behaviour.